Study on the Characteristics of the Infrared Spectrum and the Alteration Zoning of Drill Core in the Makeng Iron Deposit - SHI Wei-xin; YI Jin-jun; WANG Hao; TIAN Rong-jun (Yankuang ceshi, 2020)
BACKGROUND Silicate, sulfate, carbonate and other minerals can be identified by infrared reflectance spectroscopy which is a non-destructive and rapid batch method. In recent years, infrared reflectance spectroscopy has played an important role in mineralogical research, mineral exploration and prospecting, mining and metallurgy. Altered minerals such as pyroxene, garnet, olivine and rock-forming minerals such as feldspar and quartz can be identified rapidly with thermal infrared (6000-14500nm, TIR), which is important for mineralogical research, mineral exploration and prospecting of skarn type, copper-nickel sulfide type and quartz-vein type deposits. OBJECTIVES To quickly characterize the type and assemblage of alteration minerals. METHODS Shortwave-thermal infrared reflectance spectroscopy was used to analyze the drill cores of the Makeng iron deposit in the National Geological Archives. The spectral characteristics of the altered minerals in this deposit were summarized, the type and assemblage of alteration minerals were quickly determined. RESULTS The results showed that the altered minerals in Makeng include garnet, pyroxene, carbonate, chlorite, sericite, hornblende, epidote, montmorillonite and gypsum. There were significant reflections at 9199nm, 9730nm, 10500nm and 11100nm for garnet. For pyroxene, the significant reflections were mainly located at 11500nm and 12150nm. Infrared spectroscopy analysis showed that altered minerals displayed obvious zoning in space, and the assemblage and distribution of altered minerals were strictly controlled by the lithology of country rocks and hydrothermal metasomatism. Garnet+pyroxene can be used as the typical mineral assemblage of skarn deposits, and the characteristics of alteration zoning indicated a process from high temperature to low temperature. CONCLUSIONS Combined with the geological features, the Makeng iron deposit can be defined as a stratabound skarn deposit. This research can provide scientific support for the understanding of skarn-type deposits and related prospecting and exploration.